Telomere length, apoptotic and inflammatory genes: novel biomarkers of gastrointestinal tract pathology and meat quality traits in chickens under chronic stress (Gallus gallus domesticus) - Badmus, Kazeem Ajasa; Idrus, Zulkifli; Goh, Yong Meng; Kamalludin, Mamat Hamidi (MDPI AG, 2021)
This study was designed to examine the potentials of telomere length, mitochondria, and acute phase protein genes as novel biomarkers of gastrointestinal (GI) tract pathologies and meat quality traits. Chickens were fed a diet containing corticosterone (CORT) for 4 weeks and records on body weight, telomere length, GI tract and muscle histopathological test, meat quality traits, mitochondria, and acute phase protein genes were obtained at weeks 4 and 6 of age. The body weight of CORT-fed chickens was significantly suppressed (p < 0.05). CORT significantly altered the GI tract and meat quality traits. The interaction effect of CORT and age on body weight, duodenum and ileum crypt depth, pH, and meat color was significant (p < 0.05). CORT significantly (p < 0.05) shortened buffy coat telomere length. UCP3 and COX6A1 were diversely and significantly expressed in the muscle, liver, and heart of the CORT-fed chicken. Significant expression of SAAL1 and CRP in the liver and hypothalamus of the CORT-fed chickens was observed at week 4 and 6. Therefore, telomere lengths, mitochondria, and acute phase protein genes could be used as novel biomarkers for GI tract pathologies and meat quality traits.